U‐PB Detrital Zircon Geochronology of the Lower Danube and Its Tributaries: Implications for the Geology of the Carpathians - Mihai N. Ducea; Liviu Giosan; Andrew Carter; Constantin Balica; Adriana M. Stoica; Relu D. Roban; Ion Balintoni; Florin Filip; Lucian Petrescu (Geochemistry, Geophysics, Geosystems, 2018)
Abstract We performed a detrital zircon (DZ) U‐Pb geochronologic survey of the lower parts of the Danube River approaching its Danube delta, Black Sea sink, and a few large tributaries (Tisza, Jiu, Olt, and Siret) originating in the nearby Carpathian Mountains. Samples are modern sediments. DZ age spectra reflect the geology and specifically the crustal age formation of the source area, which in this case is primarily the Romanian Carpathians and their foreland with contributions from the Balkan Mountains to the south of Danube and the East European Craton. The zircon cargo of these rivers suggests a source area that formed during the latest Proterozoic and mostly into the Cambrian and Ordovician as island arcs and back‐arc basins in a Peri‐Gondwanan subduction setting (~600–440 Ma). The Inner Carpathian units are dominated by a U‐Pb DZ peak in the Ordovician (460–470 Ma) and little inheritance from the nearby continental masses, whereas the Outer Carpathian units and the foreland have two main peaks, one Ediacaran (570–610 Ma) and one in the earliest Permian (290–300 Ma), corresponding to granitic rocks known regionally. A prominent igneous Variscan peak (320–350 Ma) in the Danube's and tributaries DZ zircon record is difficult to explain and points out to either an extra Carpathian source or major unknown gaps in our understanding of Carpathian geology. Younger peaks corresponding to arc magmatism during the Alpine period make up as much as about 10% of the DZ archive, consistent with the magnitude and surface exposure of Mesozoic and Cenozoic arcs.